Seed potato minitubers production in a reused substrate (Bioscience Journal, 2020)
Minituber production is an important step to obtain high-quality seed potatoes. This production is carried out in a greenhouse using a large volume of commercial substrate acquired in specialized trade. An alternative to reduce the volume of substrate purchased for each production of minitubers would be to reuse it, which would be a way to optimize its use. The objective of this study was to evaluate the efficiency of reused substrates in the minituber production. The experiment was conducted in Tapira-MG with the Atlantic potato cultivar. The experimental design was a randomized block with six treatments and four replications, where each plot was represented by a box (0.15 x 0.4 x 0.5m: height, width, and length, respectively) containing substrates. Treatments consisted of formulation 04-14-08 rates (0, 25, 50, 75, and 100 g box-1) added to reused substrate and a control consisting of a new virgin substrate. At 45 days after transplanting, the following characteristics were evaluated: stem size (cm), and quantities of fresh and dry matter of aerial part of plants. Harvesting was performed manually, counting, and calculating the yield of tubers according to class. The reuse substrate with enriched nutrient regardless of the rate, when compared to the use of a new virgin substrate, did not interfere in potato plant development and in the total productivity of minitubers of classes I, II, III, and IV. This can be a feasible alternative for optimizing the use of the virgin substrate. The rate of 25 g box-1 of 4-14-8 is sufficient to provide the needs of potato in nutrients, ensuring high productivity.